Cleft lip and palate: factors that interfere with motor development in children between 0 and 18 months (Research, Society and Development, 2022)
Objectives: To investigate factors that interfere with motor development in children aged up to 18 months with cleft lip and palate. Methodology: This is an exploratory study of children aged between 0 and 18 months with cleft lip and palate. Motor development was classified according to the Alberta Infant Motor Scale (AIMS). And cleft lip and palate according to Spina's Classification. Results and Discussion: 103 children participated in the study. The most frequent type of cleft was Incomplete Post-Foramen Cleft Palate with 21.35% (n=22), more incident in females with 13.59% (n=14); and the Complete Transforamen Unilateral Cleft Lip had 12.62% (n=13), with a higher incidence in males. It was observed that the type of cleft did not present a significant correlation with any of the variables. As for motor development, it can be observed that 53.40% presented risk or delay in motor development. Conclusion: It is concluded that the motor development has factors that interfere in its evolution, being these the maternal age/education, gestational age and Apgar, however, they did not present correlation with the type of cleft.